IMPLEMENTASI MODEL DISCOVERY LEARNING DISERTAI LEMBAR KERJA SISWA DALAM PEMBELAJARAN FISIKA SISWA DI SMA - Anis Zulfah Furoidah; Indrawati Indrawati; Subiki Subiki (JURNAL PEMBELAJARAN FISIKA, 2017)
This study focus examined the implementation model discovery learning with worksheets student to physic instruction at SMA. The purposes of this research was to examine the effect model discovery learning process science skills, learning motivation, and learning achievement to physics at SMA. The population in this study was X class and the sample are X MIA-5 and X MIA-6 were of SMAN 1 Kencong. This research was a experimental with post-test only control group design. The data are collected by test, observation, interview, question form and documentation. Data analysis techniques T-test using SPSS 22. The results of study: (1) the average value of science process skills 66.8 (2) the average value of motivation 77.4 (3) the average value of learning achievement 62.6. This research can be concluded: (1) there is the effect significant of the use a model discovery learning accompanied by Worksheets Students towards science process skills students, (2) there is the effect significant of the use a model discovery learning accompanied by Worksheets Students towards the learning motivation students, (3) there is the effect significant of the use a model discovery learning accompanied by Worksheets Students toward student learning outcomes. Keywords: Model Discovery Learning, Worksheet Students, Science Process Skills, Learning Motivation, Learning Outcomes